2017
DOI: 10.1039/c6ra28615a
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study and transient CFD/DEM simulation in a fluidized bed based on different drag models

Abstract: Gas-solid two-phase flow is the main phenomena in the chemical-looping combustion (CLC) fluidized bed system. Drag force generated from relative movement between phases is the main force that hinders the movement of the oxygen carrier particles. It is important to evaluate and understand the limitations and validity range of different drag models. In this paper, based on Discrete Elements Methods (DEM) coupled with Computational Fluid Dynamics (CFD), three kinds of drag models, Wen-Yu, Syamal-O'Brien, and Gida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The validity of three drag laws (Gidaspow, Syamal-O'Brien and Wen-Yu) was tested in a spout-fluid bed by Zhou and others [111]: they reported that all three laws could accurately reproduce the spouting evolution of the bed, but the bed height was always underestimated. They identified Gidaspow law as the most accurate drag model, although pointing out that much work still has to be done in this field.…”
Section: Drag Law Number Of Occurrences Referencesmentioning
confidence: 99%
“…The validity of three drag laws (Gidaspow, Syamal-O'Brien and Wen-Yu) was tested in a spout-fluid bed by Zhou and others [111]: they reported that all three laws could accurately reproduce the spouting evolution of the bed, but the bed height was always underestimated. They identified Gidaspow law as the most accurate drag model, although pointing out that much work still has to be done in this field.…”
Section: Drag Law Number Of Occurrences Referencesmentioning
confidence: 99%
“…22 For CFD-DEM, validation of numerical results against experiments has been conducted (see a recent review by Norouzi et al). In general, it is found that CFD-DEM simulations capture the experimental observations quite well, in terms of both macroscopic (pressure drop, bed expansion, bubble size) 15,[24][25][26][27][28][29][30] and microscopic (voidage and particle velocity profiles) [31][32][33][34][35] measurements. In general, it is found that CFD-DEM simulations capture the experimental observations quite well, in terms of both macroscopic (pressure drop, bed expansion, bubble size) 15,[24][25][26][27][28][29][30] and microscopic (voidage and particle velocity profiles) [31][32][33][34][35] measurements.…”
Section: Introductionmentioning
confidence: 77%
“…23 The most commonly used system is a simple rectangular, bubbling fluidized bed containing 10 5 Geldart Group B or D particles. In general, it is found that CFD-DEM simulations capture the experimental observations quite well, in terms of both macroscopic (pressure drop, bed expansion, bubble size) 15,[24][25][26][27][28][29][30] and microscopic (voidage and particle velocity profiles) [31][32][33][34][35] measurements. Alternatively, system-size independent metrics, such as particle defluidization, 36 allow for the direct comparison between small-scale CFD-DEM simulations of fluidized beds and large-scale experiments.…”
Section: Introductionmentioning
confidence: 77%
“…In the Eulerian model, the fluid volume fraction term and the motion differential equation are respectively as Equations (1) and (2) [15,16] :…”
Section: Model Description 21 Mathematical Modelmentioning
confidence: 99%